The Role Of Operational Efficiency In Mediating The Influence Of Der, Roa, And Company Size On Operational Performance - Nur Alam Umar (Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2026)
The banking industry faces increasing competitive pressure and regulatory demands, making operational efficiency a critical determinant of organizational performance. This study examines the effects of the Debt-to-Equity Ratio (DER), Return on Assets (ROA), and firm size on operational efficiency, as well as the mediating role of operational efficiency in linking these financial characteristics to the operational performance of Indonesian banks. A quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) was applied to secondary data obtained from financial statements published by the Financial Services Authority of Indonesia (OJK). The measurement and structural models were evaluated through reliability and validity assessments, model fit evaluation, and bootstrapping procedures to test the significance of direct and indirect relationships. The findings indicate that DER, ROA, and firm size positively contribute to operational efficiency. However, their direct effects on operational performance are relatively weak, suggesting that financial strength does not automatically translate into greater asset productivity. Operational efficiency serves as the primary transmission mechanism through which financial resources are converted into improved performance, while firm size provides a comparatively more stable direct contribution. These findings confirm that operational efficiency plays a dominant role in enhancing banking performance by promoting more effective asset utilization. This study contributes to the banking literature by positioning operational efficiency as a key mediating mechanism linking financial characteristics to operational performance in Indonesia’s banking sector.